القضية الجزائرية في الصحافة الكويتية جريدة الفجر -أنمــــــوذجــــــا- 1956م - 1958م - بلعيد هادية; بابا عربي نجيبة (University Of Eloued جامعة الوادي, 2024)
تفاعل الاعلام العالمي مع الثورة الجزائرية خاصة الصحافة العربية، منها جريدة الفجر الكويتية تناولت القضية الجزائرية مابين 1956-1958 وهي موضوع دراستنا . توصلنا من خلالها لعدة نتائج اهمها : التعريف بجريدة الفجر الكويتية ودورها في دعم القضية الجزائرية وقضايا التحرر ، وإبراز دور الصحافة العربية في إذكاء روح القومية العربية. The world media interacted with the Algerian revolution, especially the Arab press, including the Kuwaiti newspaper Al-Fajr, which dealt with the Algerian case between 1956 and 1958, which is the subject of our study. Through it, we have reached several important conclusions: the introduction of the Kuwaiti Dawn newspaper and its role in supporting the Algerian cause and liberation issues, and the visibility of the Arab press in promoting the spirit of Arab nationalism.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: القضية الجزائرية; The Algerian issue; الثورة الجزائرية; Algerian Revolution; الصحافة الكويتية; Kuwaiti press